The Influence of Social Media Marketing and Electronic Word of Mouth on Purchase Intention of Sea Makeup Products through Brand Image on the TikTok Platform in Pekanbaru City - Revi Marita; Prima Andreas; Dian Pratiwi; Henni Noviasari (Westscience Press, 2026)
This study aims to analyze the influence of social media marketing and electronic word of mouth on purchase intention through brand image for Sea Makeup products on the TikTok platform in Pekanbaru City. The background of this study is based on the rapid growth of TikTok as a digital marketing platform that plays an important role in shaping consumer perceptions and purchase intentions, especially among Generation Z. The pre-survey results indicate that although content exposure is relatively high, consumer perceptions of the product remain varied. This study employs a quantitative approach using purposive sampling techniques involving 190 Generation Z women respondents in Pekanbaru City. Data were collected through a Likert-scale questionnaire and analyzed using the SEM-PLS method with the assistance of SmartPLS 4. The results show that social media marketing and e-WOM have a positive and significant effect on brand image and purchase intention. In addition, brand image also has a significant effect on purchase intention and is able to mediate the influence of social media marketing and e-WOM on purchase intention. These findings indicate that digital marketing activities and user interactions on TikTok play an important role in shaping brand image and increasing consumer purchase intention.